2019
DOI: 10.3389/fneur.2019.00754
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: Etiologic and Molecular Mechanistic Leads for Sporadic Neurodegenerative Diseases Based on Experience With Western Pacific ALS/PDC

Abstract: Seventy years of research on Western Pacific amyotrophic lateral sclerosis and Parkinsonism-dementia Complex (ALS/PDC) have provided invaluable data on the etiology, molecular pathogenesis and latency of this disappearing, largely environmental neurodegenerative disease. ALS/PDC is linked to genotoxic chemicals (notably methylazoxymethanol, MAM) derived from seed of the cycad plant ( Cycas spp.) that were used as a traditional food and/or medicine in all three disease-affected Western Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 132 publications
0
30
0
Order By: Relevance
“…It was commonly believed by mushroom pickers that this species was not toxic since contradictory poisoning experience was reported. As a result, it is found as edible in mushroom lists proposed in France and Finland [ 16 ] and reported as gourmet food or as rejuvenating [ 9 , 13 ]. As popular belief is hard to change, its deliberate consumption was also reported in the Scandinavian countries.…”
Section: False and True Morels And Reported Toxic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was commonly believed by mushroom pickers that this species was not toxic since contradictory poisoning experience was reported. As a result, it is found as edible in mushroom lists proposed in France and Finland [ 16 ] and reported as gourmet food or as rejuvenating [ 9 , 13 ]. As popular belief is hard to change, its deliberate consumption was also reported in the Scandinavian countries.…”
Section: False and True Morels And Reported Toxic Effectsmentioning
confidence: 99%
“…The toxic compounds responsible for this acute toxicity are not known. However, the presence in the various Agaricus spp of a natural toxicant called agaritine and containing an hydrazinic moiety in its structure is worth considering, since toxicity of hydrazine derivatives, due to their high reactivity as chemical radicals, has been known for years [ 13 , 45 , 46 ]. Furthermore, curiously, agaritine poisoning is less and less mentioned in the recent literature except in two isolated studies published in 2014 [ 5 , 33 ] and an up to date is necessary.…”
Section: Button Mushroom (And Agaricus Spp) Anmentioning
confidence: 99%
See 1 more Smart Citation
“…As A-T, there are Nijmegen breakage syndrome (NBS), Bloom syndrome (BS), and A-T-like disorder, all of which are characterized by chromosomal instability, neurodegeneration, oxidative stress, and immunodeficiency [ 11 ]. DNA damage, cell-cycling abnormalities, cerebellar pathology, tauopathy linked to the production of Reactive Oxygen Species (ROS), and alterations in epigenetic pathways have also been demonstrated in the Western Pacific Amyotrophic Lateral Sclerosis and Parkinsonism-dementia Complex (ALS/PDC) syndrome [ 49 ]. Accordingly, in a recent study, TDP-43, which has been shown to participate in DNA repair pathways, has been found in the tau-dominated polyproteinopathy of Western Pacific ALS/PDC [ 50 ], in particular in the spinal cord, limbic, and cortical regions of patients.…”
Section: Atm Governs Genomic Integritymentioning
confidence: 99%
“…The role of environmental factors has been frequently reported in systematic reviews and meta-analysis of observational studies (see for example Yu et al, 2014;Oskarsson et al, 2015;Bozzoni et al, 2016;Wang et al, 2017;Riancho et al, 2018). Toxins from cyanobacteria, infectious agents, and mushrooms (Cox et al, 2016;Castanedo-Vazquez et al, 2019;French et al, 2019;Spencer et al, 2019;Fiore et al, 2020), hydrazine from fungal or industrial origin (Spencer, 2019;Spencer et al, 2019), cigarette smoking (Calvo et al, 2016), alcohol consumption (de Jong et al, 2012), physical work (Huisman et al, 2013), agonistic sport activities (Chiò et al, 2005;Gotkine et al, 2014;Visser et al, 2019), military service (Binazzi et al, 2009;Drouet et al, 2010;Beard and Kamel, 2015), head trauma (Filippini et al, 2020a;McKee et al, 2010;Seelen et al, 2014), exposure to electromagnetic fields (Hakansson et al, 2003;Gunnarsson and Bodin, 2018), pesticides (Chiò et al, 2009;Malek et al, 2012;Kamel et al, 2012;Vinceti et al, 2012;Vinceti et al, 2017), and Pb (Filippini et al, 2020b;Oh et al, 2007) are the environmental culprits most commonly cited for ALS (Zufiria et al, 2016), sometimes in controversial ways.…”
Section: Introductionmentioning
confidence: 99%